Dziecko z chorobą przewlekłą w systemie oświaty - Serafin, Teresa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Article with the chronic illness in the school system shows a sectioned regulations rela- ting to the provision of medical and psycho-educational school environment. Draws attention system chronically ill children can attend any school perimeter and get in the psycho-pedagogical assistance and identifies principles for implementing this aid, and for those children and yang people with the panel public psychological and pedagogical issued judgment about the need for individual teaching – they can purse teaching in the place of residence or in the separate room in the school – if it is clear the recommendations of the judgment. However, for children who need to be hospitalized organized learning activities and special care in schools operating in this therapeutic entities.